2020
DOI: 10.1589/jpts.32.524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an external foci of attention at different distances on standing long jump in non-athletes

Abstract: [Purpose] External focus (EF) instructions demonstrate a learning effect on motor performance enhancement. However, the effective EF distance during standing long jump performance of non-athletes has not been clarified. This study aimed to determine the effects of EF at different distances on jumping performance. [Participants and Methods] A total of 40 non-athlete participants were randomly divided among four groups. The no attention line group performed a standing long jump without the attention line on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Findings from this study confirmed earlier work from McNevin et al, [11] as the data showed that horizontal jump distance was systematically increased as attention was directed at spatially greater distances from the mover. Since the aforementioned findings, much research using the SLJ has been conducted exploring the distance effect on motor learning and performance with regard to the external far condition [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study confirmed earlier work from McNevin et al, [11] as the data showed that horizontal jump distance was systematically increased as attention was directed at spatially greater distances from the mover. Since the aforementioned findings, much research using the SLJ has been conducted exploring the distance effect on motor learning and performance with regard to the external far condition [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This differs from previous investigations as this study specifically examined how various internal foci impact motor performance. Based on previous attentional focus work using the SLJ task [12][13][14]16,20,22,[27][28][29][30], it was predicted that worse performances would be observed in all internal focus conditions compared to a control condition. Additionally, it was predicted that there would be no significant differences between the IFOA conditions.…”
Section: Introductionmentioning
confidence: 99%